Assessment of risk for periodontal disease. I. Risk indicators for attachment loss - Grossi, S G; Zambon, J J; Ho, A W; Koch, G; Dunford, R G; Machtei, E E; Norderyd, O M; Genco, R J (Journal of periodontology (1970), 1994)
Specific risk indicators associated with either susceptibility or resistance to severe forms of periodontal disease were evaluated in a cross-section of 1,426 subjects, 25 to 74 years of age, mostly metropolitan dwellers, residing in Erie County, New York, and surrounding areas. The study sample exhibited a wide range of periodontal disease experience defined by different levels of attachment loss. Therefore, it was possible to accurately assess associations between the extent of periodontal disease and patient characteristics including age, smoking, systemic diseases, exposure to occupational hazards, and subgingival microbial flora. Age was the factor most strongly associated with attachment loss, with odds ratios for subjects 35 to 44 years old ranging from 1.72 (95% CI: 1.18 to 2.49) to 9.01 (5.86 to 13.89) for subjects 65 to 74 years old. Diabetes mellitus was the only systemic disease positively associated with attachment loss with an odds ratio of 2.32 (95% CI: 1.17-4.60). Smoking had relative risks ranging from 2.05 (95% CI: 1.47-2.87) for light smokers increasing to 4.75 (95% CI: 3.28-6.91) for heavy smokers. The presence of two bacteria, Porphyromonas gingivalis and Bacteroides forsythus, in the subgingival flora represented risks of 1.59 (95% CI: 1.11-2.25) and 2.45 (95% CI: 1.87-3.24), respectively. Our results show that age, smoking, diabetes mellitus, and the presence of subgingival P. gingivalis and B. forsythus are risk indicators for attachment loss. These associations remain valid after controlling for gender, socioeconomic status, income, education, and oral hygiene status expressed in terms of supragingival plaque accumulation and subgingival calculus. Longitudinal, intervention, and etiology-focused studies will establish whether these indicators are true risk factors.